Identification of Allelic Variation in Drought Responsive Dehydrin Gene Based on Sequence Similarity in Chickpea (Cicer arietinum L.) - Kumar, Tapan; Tiwari, Neha; Bharadwaj, Chellapilla; Sarker, Ashutosh; Pappula, Sneha Priya Reddy; Singh, Sarvjeet; Singh, Mohar (Frontiers in Genetics, 2020)
Chickpea (Cicer arietinum L.) is an economically important food legume grown in arid and semi-arid regions of the world. Chickpea cultivated mainly in rainfed condition in the residual moisture and restricted irrigation condition. The crop is prone to drought stress which results in retardation of flowering and major yield loss in many parts of the world. The present study provides a comparative study of a candidate gene, molecular marker, and physiological traits for screening drought tolerance in chickpea. Abiotic stress-responsive gene Dehydrin (DHN) also identified in some of the chickpea genotypes based on the sequence similarity approach. Based on morphological data analysed for drought stress including relative water content and Membrane stability index and yield in comparison to normal condition the genotypes According to the study, analysis of variance, there were significant effects of drought stress on RWC, MSI, plant height, and yield traits. The Pusa1103 and Pusa362 well-known donor along with ICC4958 were found most promising genotypes for drought tolerance as they maintained the higher value of RWC, MSI, plant height, and yield traits. The results were further supported by, sequence similarity approach when analysed for the presence of single nucleotide polymorphisms (SNPs) and indels. Homozygous indels and SNPs were found after the sequencing in some tolerant genotypes